Prognostic role of demographic indicators and Charlson comorbidity index in oxygen-dependent patients with coronavirus disease (COVID-19) - Cherkaskyi, V. V.; Riabokon, O. V.; Riabokon, Yu. Yu.; Черкаський, Володимир Васильович; Рябоконь, Олена Вячеславівна; Рябоконь, Юрій Юрійович (Запорізький державний медичний університет, 2022)
Aim. The aim of our work is to establish the prognostic significance of demographic indicators and the Charlson comorbidity index (CCI) in oxygen-dependent patients with coronavirus disease (COVID-19). Material and methods. The research included 211 oxygen-dependent patients with COVID-19: I group – 94 patients who recovered; II group – 117 patients, the disease ended fatally. We used the WHO age classification when analyzing the age structure of patients. The Charlson comorbidity index was calculated for each patient. The patients were divided into groups Statistical data processing was carried out in the program Statistica for Windows 13 (StatSoft Inc., No. JPZ804I382130ARCN10-J). Results. It was established that the median age of the ІІ group patients was higher (P < 0.001) than patients the I in group. Elderly patients were more often registered in the ІІ group than among patients in group I (25.6 % vs. 8.5 %, P = 0.001). Middle-aged patients were more often registered in the І group than among patients in the II group (34.0 % vs. 19.4 %, P = 0.02). According to the result of the ROC analysis, the prognostic value of the age of the patients was established, namely, under conditions of age >66 years (AUC = 0.636, Р = 0.002), the probability of a fatal outcome of COVID-19 was significant. Мета роботи – встановити прогностичну значущість демографічних показників та індексу коморбідності Charlson у кисневозалежних хворих на коронавірусну хворобу (COVID-19). Матеріали та методи. У дослідження залучили 211 кисневозалежних хворих на COVID-19: I група – 94 пацієнти, які одужали; II група – 117 осіб, у котрих захворювання завершилося летально. Під час аналізу вікової структури хворих користувалися класифікацією віку ВООЗ (2015). У кожного пацієнта розраховували індекс коморбідності Charlson (CCI). Статистичне опрацювання здійснили в програмі Statistica for Windows 13 (StatSoft Inc., № JPZ804I382130ARCN10-J). Результати. Встановлено, що у хворих ІІ групи медіана віку вища (р < 0,001), ніж у хворих I групи. У ІІ групі було більше пацієнтів старечого віку, ніж у I (25,6 % проти 8,5 %, р = 0,001), а пацієнтів середнього віку було більше у І групі, ніж у II (34,0 % проти 19,4 %, р = 0,02). За результатами ROC-аналізу встановлена прогностична цінність віку пацієнтів. Так, якщо вік хворого становив >66 років (AUC = 0,636, р = 0,002), імовірність летального результату COVID-19 значуща.
Прогностична роль демографічних показників та індексу коморбідності Charlson у кисневозалежних хворих на коронавірусну хворобу (COVID-19)
Cherkaskyi V. V. - ORCID ID: 0000-0003-2959-8803; Riabokon O. V. - ORCID ID: 0000-0002-7394-4649; Riabokon Yu. Yu. - ORCID ID: 0000-0002-2273-8511.
Keywords: coronavirus disease COVID-19; viral infection; comorbidity; risk factors; prognosis; коронавірусна хвороба COVID-19; вірусна інфекція; коморбідність; фактори ризику; прогноз